2022
DOI: 10.1177/09732179221100609
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Scrub Typhus—A Case Report

Abstract: Scrub typhus is the most common rickettsial infection in India. A neonate with suspected late-onset sepsis/late hemorrhagic disease of newborn and scrotal cellulitis was finally diagnosed as scrub typhus. The samples of blood and urine were sent and azithromycin was started empirically awaiting the reports. The baby improved with resolution of fever and increased oral acceptance and thrombocytopenia resolved. In any newborn presenting with fever, eschar, and positive family history, besides other common diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Among others, the baby described in our case also had thrombocytopaenia, fever, hepatosplenomegaly and shock. Vertical transmission confirmed by positive serology for scrub typhus was reported in four cases 5–7 15. Among the cases where vertical transmission was suspected, PCR was either not done or negative in three of the cases,5 6 15 and positive in one7 but none of the previously reported studies reported on maternal PCR.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Among others, the baby described in our case also had thrombocytopaenia, fever, hepatosplenomegaly and shock. Vertical transmission confirmed by positive serology for scrub typhus was reported in four cases 5–7 15. Among the cases where vertical transmission was suspected, PCR was either not done or negative in three of the cases,5 6 15 and positive in one7 but none of the previously reported studies reported on maternal PCR.…”
Section: Discussionmentioning
confidence: 84%
“…Vertical transmission confirmed by positive serology for scrub typhus was reported in four cases 5–7 15. Among the cases where vertical transmission was suspected, PCR was either not done or negative in three of the cases,5 6 15 and positive in one7 but none of the previously reported studies reported on maternal PCR. PCR was positive in both the neonate and the mother in our case, making the evidence for vertical transmission more robust.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Treatment should continue until the patient becomes afebrile for 3 days or 7–10 days. However, some experts disagree with doxycycline as the first choice of treatment, particularly in neonates, because of its potential side effects, and instead prefer azithromycin and clarithromycin ( 24 ). Macrolides, including azithromycin, are considered safe for use during pregnancy and in young children, with a recommended dose of 10 mg/kg/day (maximum 500 mg) for 5 days ( 2 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%